Obnova hradov na území Slovenska - Ondrejková, Zuzana (Univerzita Pardubice, 2014)
The theme of the article is castle restoration in Slovakia. The article is focused on methodology of restoration used in castle restoration and on determinants that affects its selection. The research is mapping development of castle restorations on the territory of present day Slovakia. Article introduces characteristical castle restoration waves. Castle restoration begins in late 18. century, trough monument restoration institutionalization in 19. century and characteristical restoration decades in 20. century, until present day trends. Preliminary results of field research show specifics of current castle restoration in comparison with pervious castle restoration waves. Quantity of currently restored castles demanded strictly conservative approach, which has no equivalent in Slovakia monument restoration history. Typical Slovakia castle restoration representatives for each restoration wave are introduced in this article. Each chosen castle represents the use of one method of restoration. The aim of the study is to sum and evaluate implemented choosen castle restorations in Slovakia.
Castle restoration in Slovakia